Peran Hukum Alam dalam Menjawab Tantangan dan Peluang Regulasi Deforestasi Uni Eropa terhadap Perdagangan Berkelanjutan Indonesia. - Alvianto, Danang; Sutrisno, Andri; Wendra, Muhammad (Harmonization : Jurnal Ilmu Sosial, Ilmu Hukum, dan Ilmu Ekonomi, 2024)
The European Union Deforestation Regulation (EUDR), implemented in 2023, requires transparent supply chains to prevent imported products from contributing to illegal deforestation, presenting both challenges and opportunities for Indonesia as a leading exporter of palm oil and timber. This study explores how natural law principles, emphasizing ecological justice and the moral balance between humans and nature, can serve as an ethical foundation to meet EUDR requirements. By integrating these principles into policy reforms such as enhancing the Indonesia Sustainable Palm Oil (ISPO) certification, investing in green technologies, and fostering international collaboration, Indonesia can overcome economic barriers and lead in sustainable trade.